Electrochemical comparison of two methods for polythionineelectropolymerization and its relevance as amperometric detector - Farias, Eliana Desiree (2013)
The electrochemical behavior of polythionine on different electrodes has been investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Polymeric films were obtained by two electropolymerization methods: M1 using cyclic voltammetry or M2 in two steps, a constant potential oxidation and cycle potential sweeps. Those methodologies were compared by analyzing the electrochemical behavior of the films using two redox probes. The modified surfaces were also analyzed as electroanalytical sensors so phenol response was tested and a simple and reliable method for phenol quantification was proposed and validated, corresponding to an M2 glassy carbon modified electrode, using a 0.7 V working potential with a 4 × 10-6 to 2.7 × 10-5 M linear range, with those conditions a 3.6 × 10-6 mol L-1 LOD, 1.09 × 10-5 mol L -1 LOQ and a (2.9 ± 0.2) × 107 C Phenol (mol L-1) sensitivity are obtained.